EFFICIENT DSP-BASED REAL-TIME IMPLEMENTATION OF ANFIS REGULATOR FOR SINGLE-PHASE POWER FACTOR CORRECTOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
As a widely used technology, active power factor corrector (A-PFC) circuits face many control challenges, such as nonlinearity and uncertainties. With more and more power electrical appliances that are connected to the utility grid, the A-PFC is for the task of improving the power quality (PQ) to meet the requirement of the international standards, and this results in great challenges for keeping the total harmonic distortion (THD) as long as a power factor in the desired ranges. To this end, this paper focuses on the simulation and real-time implementation of a combined adaptive neural-fuzzy inference system (ANFIS) and predictive current controller for a single-phase PFC rectifier. The proposed control method has a simple, low-cost structure for better response and robustness. The performance of the proposed control approach was evaluated in real-time based on the dSPACE 1104 digital signal processor for different reference and load conditions. The results obtained from simulation and experimental tests validate the superiority of the proposed approach by evidencing a unity power factor, lower THD, fast dynamic response, and robustness against fast load and output voltage variations.
Keywords: Active power factor correction (A-PFC) converter; Adaptive neural-fuzzy inference system (AN-FIS); Predictive current controller; dSPACE card 1104